2020
DOI: 10.1016/j.spa.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

A semigroup approach to nonlinear Lévy processes

Abstract: We study the relation between Lévy processes under nonlinear expectations, nonlinear semigroups and fully nonlinear PDEs. First, we establish a one-toone relation between nonlinear Lévy processes and nonlinear Markovian convolution semigroups. Second, we provide a condition on a family of infinitesimal generators (A λ ) λ∈Λ of linear Lévy processes which guarantees the existence of a nonlinear Lévy process such that the corresponding nonlinear Markovian convolution semigroup is a viscosity solution of the full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 20 publications
1
62
0
Order By: Relevance
“…Examples in this direction are the notions of g-Brownian motion and G-Brownian motion referring to a Brownian motion with drift or volatility uncertainty, see Peng (1997Peng ( , 2007a and references therein. Most recently, this theory has been extended to more general approaches, so-called non-linear Lévy processes, see Neufeld and Nutz (2017) and Denk et al (2017) in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Examples in this direction are the notions of g-Brownian motion and G-Brownian motion referring to a Brownian motion with drift or volatility uncertainty, see Peng (1997Peng ( , 2007a and references therein. Most recently, this theory has been extended to more general approaches, so-called non-linear Lévy processes, see Neufeld and Nutz (2017) and Denk et al (2017) in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Corollary 4.2 generalizes [23] where it was shown that u(t, x) = sup P∈Px E P f (X t ) is a viscosity solution to (16) under the additional assumptions that f is Lipschitz continuous and that sup α∈I ∫ y >1 y ν α (dy) < ∞. Recently, Denk et al [8] studied semigroups associated with Lévy processes for sublinear expectations and showed that (15) implies the existence of a viscosity solution to (16) For the particular case that the index set I consists of a finitely many elements, the tightness condition (13) is automatically satisfied, and therefore Corollary 4.2 gives the following result for classical Lévy processes.…”
Section: Corollarymentioning
confidence: 91%
“…Since the proof of the maximal inequality for Feller processes relies essentially on Dynkin's formula, we can extend it to our framework. ⋅)), x ∈ R d , α ∈ I, be a family of Lévy triplets which is uniformly bounded on compact sets, i. e. which satisfies (8). For a given truncation function h denote by…”
Section: Maximal Inequality For Sublinear Expectationsmentioning
confidence: 99%
See 2 more Smart Citations